2008
DOI: 10.1016/j.diagmicrobio.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic utility of a whole-blood interferon-γ assay for determining the risk of exposure to Mycobacterium tuberculosis in Bacille Calmette-Guerin (BCG)-vaccinated individuals

Abstract: We evaluated the utility of the "QuantiFERON®-TB Gold in tube" (QuantiFERON®) test that uses TB-specific antigens for the diagnosis of latent infection in such individuals. We also examined the correlation between the IFN-γ response to these antigens and the exposure risk to TB by evaluating antigen-specific IFN-γ release in comparison with IFN-γ release in response to PPD in three groups; medical students, nurses in a TB hospital, and TB patients. All nurses and TB patients responded to PPD whereas 79.2 % (p=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…df: degrees of freedom. [34] BABA [25] BIANCHI [28] BARTU [27] DHEDA [32] DHEDA [17] GOLETTI [35] CHEGOU [31] EUM [34] BABA [25] BIANCHI [28] BARTU [27] DHEDA [32] DHEDA [17] GOLETTI [35] CHEGOU [31] EUM [34] BABA [25] BIANCHI [28] BARTU [27] DHEDA [32] DHEDA [17] GOLETTI [35] [37] GOLETTI [36] KIM [39] KIM [41] KIM [40] KOBASHI [42] LOSI [19] MEIER [44] JAFARI [14] JAFARI [16] NICOL [45] DHEDA [32] DHEDA [17] GOLETTI [35] The situation is different in extrasanguinous samples, where the pooled sensitivity was significantly higher for T-SPOT.TB1 (88%) compared with QFT-G-IT (48%). In addition, the specificity of T-SPOT.TB1 in extrasanguinous samples was higher compared to that recorded in blood (82% versus 59%), whereas specificity of QFT-G-IT did not differ in the two compartments (79% versus 82%).…”
Section: Discussionmentioning
confidence: 99%
“…df: degrees of freedom. [34] BABA [25] BIANCHI [28] BARTU [27] DHEDA [32] DHEDA [17] GOLETTI [35] CHEGOU [31] EUM [34] BABA [25] BIANCHI [28] BARTU [27] DHEDA [32] DHEDA [17] GOLETTI [35] CHEGOU [31] EUM [34] BABA [25] BIANCHI [28] BARTU [27] DHEDA [32] DHEDA [17] GOLETTI [35] [37] GOLETTI [36] KIM [39] KIM [41] KIM [40] KOBASHI [42] LOSI [19] MEIER [44] JAFARI [14] JAFARI [16] NICOL [45] DHEDA [32] DHEDA [17] GOLETTI [35] The situation is different in extrasanguinous samples, where the pooled sensitivity was significantly higher for T-SPOT.TB1 (88%) compared with QFT-G-IT (48%). In addition, the specificity of T-SPOT.TB1 in extrasanguinous samples was higher compared to that recorded in blood (82% versus 59%), whereas specificity of QFT-G-IT did not differ in the two compartments (79% versus 82%).…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies26 30 32 35 36 40 42 43 46 49 50 52 55 57 reported a positive association between IGRA positivity and occupational risk factors, including higher risk for clinical staff working in a high-risk ward, TB clinic or geriatric care and increased duration of healthcare employment. Two studies38 39 reported no association between test positivity and risk factors; the remaining studies either did not perform the TST or did not calculate ORs for risk factors associated with test positivity.…”
Section: Resultsmentioning
confidence: 99%
“…However, current diagnostic methods have limited use, because only 5-16% of children with suspected TB have positive acid fast bacillis smears and positive cultures are reported in only 20-50% of suspected cases (36)(37)(38)(39)(40)(41)(42)(43)(44). Although commercial IFN-g release assays are more specific than the TST in adults (45) and children (46), IFN-g release assays have limited use in TB-endemic settings because they do not reliably differentiate TB from latent TB (47)(48)(49). In this regard, we also found that measurement of ESAT-6/CFP-10-specific PBMC responses did not distinguish healthy children exposed to Mtb from children with TB.…”
Section: Discussionmentioning
confidence: 99%